INVESTIGATION OF SINGLE-PHASE SHORT CIRCUIT IN NETWORKS WHEN THE TRANSFORMER IS CONNECTED WITH THE NEUTRAL GROUND (Academia Science Repository, 2023)
The article deals with the resonant connection of the neutral to the ground. In these experiments, it was considered that the change of the single-phase ground current, the change of the phase voltages depends on the change of the values of active and inductive resistance in cases where the neutral of the transformer is connected in different ways.